2018
DOI: 10.1002/iub.1749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol on doxorubicin resistance in breast neoplasm cells by modulating PI3K/Akt signaling pathway

Abstract: In the study, we probed into the effect of Resveratrol (RES) on Doxorubicin (DOX)-resistant breast neoplasm cell line MCF-7/DOX as well as the mechanism of RES underlying the DOX-resistant breast cancer. CCK-8 assay was utilized to assess the survival rates and sensitivity of breast neoplasm cell lines MCF-7 or MDA-MB-231 to DOX and RES. DOX-resistant MCF-7 cell line was successfully cultivated with DOX dose increasing and was named MCF-7/DOX. Afterwards, wound healing and Transwell assays were performed to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…Adriamycin could diffuse into the nucleus of HCC cells, interact with DNA and eventually induce apoptosis. There are some known mechanisms for development of adriamycin resistance of HCC [68][69][70][71][72][73][74][75]. Multiple miRNAs have been reported to be involved in adriamycin resistance in HCC ( Table 2).…”
Section: Mirnas and Resistance To Adriamycinmentioning
confidence: 99%
“…Adriamycin could diffuse into the nucleus of HCC cells, interact with DNA and eventually induce apoptosis. There are some known mechanisms for development of adriamycin resistance of HCC [68][69][70][71][72][73][74][75]. Multiple miRNAs have been reported to be involved in adriamycin resistance in HCC ( Table 2).…”
Section: Mirnas and Resistance To Adriamycinmentioning
confidence: 99%
“…CYP1B1 inhibitors have also been shown to enhance the chemotherapeutic effects of DOX in several cancer cell lines including lung cancer [192][193][194], breast cancer [195][196][197][198][199][200][201], liver cancer [201][202][203][204], glioblastoma [205], prostate cancer [206], colorectal cancer [207,208], gastric cancer [209], and leukemia [210,211]. Importantly, several inhibitors have also been shown to overcome DOX resistance in DOX-resistant cancer cell lines [209,210,[212][213][214][215][216][217]. Although all these compounds (Table 3) are known inhibitors of CYP1B1, the role of CYP1B1 in mediating the chemosensitizing effects of these compounds have not been determined in the summarized studies.…”
Section: Chemosensitizing Effects Of Cyp1b1 Inhibitorsmentioning
confidence: 99%
“…Literature also reported that enhancement of cellular uptake of DOX was achieved due to the inhibition of the activity of P-glycoprotein(P-gp) by the RESV. P-gp is an ATP-binding cassette protein found on the cell membrane that pumps many foreign substances including drugs out of cells [ 13 , 58 ].…”
Section: Resultsmentioning
confidence: 99%